Urban and Periurban agricultural land in African cities (Yaounde and Accra) : intermediate spaces in geography - (:unkn) unknown (My University, 2011)
In sub-saharan Africa, metropolises propser bringing chanllenges and hope. The rural regions are in crisis and the rates of urban growth explode, raising the inevitable problem of the food supply of the urban population. The urban and periurban agriculture is very present because she answers number of issues of the African cities: it provides income to agricultural populations, in particular the migrants; it supplies perishable foodstuffs adapted to the urban market, like vegetables and meat; and it allows the development of unbuildable or periurban zones while the public intervention is insufficient inthis domain. The urban and periurban agriculture in the South is multifunctional. However it is little recognized by institutions and rarely included in the urban plans of development, what burdens its future and its durability. The peculiarity of this agriculture is to be in competition with the urban activities for the resources, in particular for the land. In two cities, Yaounde and Accra, the agricultural activity tooks place in specific spaces, shoals, open space, unbuildable grounds, gardens andbackyards, plots of land which wait to be built, threatened periurban villages, etc. It deploys on intermediate spaces, between the rural and the urban, between the common law and the legal right, between the tradition and the modernity.According to the age, to the genre and to the position in the customary and family hierarchy, the rights are different, whether it is to cultivate, to give or rent or to sell, without forgetting the legal procedures which grant a land title. The strategies of production depend largely on the access to the land and contrary to what takes place generally in rural areas, it are not necessarily the ones which have most land security which are the most innovative.
Keywords: African Research